Agrobacterium tumefaciens-Mediated Transformation of the Aquatic Fungus Phialemonium inflatum FBCC-F1546 - Jonghan Yoon; Youngjun Kim; Seoyeon Kim; Haejun Jeong; Jiyoon Park; Min-Hye Jeong; Sangkyu Park; Miju Jo; Sunmin An; Jiwon Park; Seol-Hwa Jang; Jaeduk Goh; et al. (Journal of Fungi, 2023)
Phialemonium inflatum is a useful fungus known for its ability to mineralise lignin during primary metabolism and decompose polycyclic aromatic hydrocarbons (PAHs). However, no functional genetic analysis techniques have been developed yet for this fungus, specifically in terms of transformation. In this study, we applied an Agrobacterium tumefaciens-mediated transformation (ATMT) system to P. inflatum for a functional gene analysis. We generated 3689 transformants using the binary vector pSK1044, which carried either the hygromycin B phosphotransferase (hph) gene or the enhanced green fluorescent protein (eGFP) gene to label the transformants. A Southern blot analysis showed that the probability of a single copy of T-DNA insertion was approximately 50% when the co-cultivation of fungal spores and Agrobacterium tumefaciens cells was performed at 24–36 h, whereas at 48 h, it was approximately 35.5%. Therefore, when performing gene knockout using the ATMT system, the co-cultivation time was reduced to ≤36 h. The resulting transformants were mitotically stable, and a PCR analysis confirmed the genes’ integration into the transformant genome. Additionally, hph and eGFP gene expressions were confirmed via PCR amplification and fluorescence microscopy. This optimised transformation system will enable functional gene analyses to study genes of interest in P. inflatum.